ANALISIS KEBIJAKAN PENDIDIKAN TENTANG PENDIDIK DAN TENAGA KEPENDIDIKAN - Hasma. B; Awaliah Musgamy (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This research aims to analyze and synthesize various literature related to education policy and education personnel in Indonesia through a systematic literature review approach. The focus of the study covers three main aspects: (1) implementation of national education policies, (2) development of the competence of education personnel, and (3) effectiveness of policies in improving the quality of education. The research method uses a systematic literature review by analyzing scientific articles, policy documents and research results published in the 2018-2023 period. A literature search was carried out through the Google Scholar, SINTA and Garuda Portal databases using relevant keywords. Of the total of 150 articles identified, 50 articles that met the inclusion criteria were analyzed in depth. The research results show several important findings: First, there is a gap between the formulation and implementation of education policies in the field. Second, developing the competence of educational staff still faces various structural and technical challenges. Third, the effectiveness of education policies is strongly influenced by leadership factors, organizational culture and stakeholder support. This research provides recommendations for improving education policies and developing education personnel in Indonesia.